Epidemiology Key to Prevention - Krickeberg, Klaus; Pham, Van Trong; Pham, Thi My Hanh.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
This book is meant for adoption in first courses on epidemiology in Medical Schools and Faculties of Public Health in developing and transition countries and in workshops in these countries, taught for example by members of international organizations. It is also suitable for parallel or second reading within curricula in developed countries and for teaching epidemiology in a Master$1 (Bs programme on (3z(BInternational Health(3y(B. The book will enable any lecturer to compose his or her introductory courses on epidemiology by selecting the material deemed appropriate. It will provide a solid foundation for more advanced teaching. The intended readership consists in the first place of general medical students; students following the programme (3z(BPreventive Physician(3y (Bthat runs parallel to general medical studies in some countries; students starting to specialize in Public Health; and lecturers in epidemiology. The book can also serve well as an introduction into epidemiology for anybody else interested in this field, for example staff of health institutions. Examples and practical work are taken from the present situation of health in Vietnam, which can easily be adapted to any other developing or transition country.s
The idea of epidemiology -- Uses and applications of epidemiology -- Some case studies and situation analyses -- Infectious diseases: descriptive epidemiology, transmissions, surveillance, control -- Infectious diseases: modelling, immunity -- Diarrhoea and cholera -- Tuberculosis and malaria -- Dengue fever -- Viral hepatitis -- HIV/AIDS -- The origin of information: registers and health information systems -- The origin of information: sampling -- Descriptive data analysis and statistics -- The normal law and applications -- Basic concepts of epidemiology -- Cross sectional studies -- Cohort studies -- Clinical (therapeutic trials) -- Clinical epidemiology -- Case control studies -- Confouding -- Epidemiology of cancer -- Epidemiology of cardio vascular diseases -- Community studies -- Nutritional and environmental epidemiology -- Social and genetic epidemiology -- Some practical considerations around epidemiologic studies -- Outlook.
Keywords: Medicine; Epidemiology; Statistical methods; Statistics; Medicine & Public Health; Epidemiology; Biostatistics; Statistics for Life Sciences, Medicine, Health Sciences